2014
DOI: 10.1136/bmjqs-2013-002776
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the electronic transmission of prescriptions on dispensing errors and prescription enhancements made in English community pharmacies: a naturalistic stepped wedge study

Abstract: ObjectivesTo compare prevalence and types of dispensing errors and pharmacists’ labelling enhancements, for prescriptions transmitted electronically versus paper prescriptions.DesignNaturalistic stepped wedge study.Setting15 English community pharmacies.InterventionElectronic transmission of prescriptions between prescriber and pharmacy.Main outcome measuresPrevalence of labelling errors, content errors and labelling enhancements (beneficial additions to the instructions), as identified by researchers visiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…Community pharmacy dispensing errors could be reduced through electronic transmission of prescriptions from general practice to the dispensing community pharmacy, as this would prevent errors at the prescriber–dispenser interface [74]. We also recommend implementing a bar coding system for all medications (as is often done in hospital pharmacies), to reduce the potential for human error by acting as an additional safety check prior to medication dispensing [7577].…”
Section: Discussionmentioning
confidence: 99%
“…Community pharmacy dispensing errors could be reduced through electronic transmission of prescriptions from general practice to the dispensing community pharmacy, as this would prevent errors at the prescriber–dispenser interface [74]. We also recommend implementing a bar coding system for all medications (as is often done in hospital pharmacies), to reduce the potential for human error by acting as an additional safety check prior to medication dispensing [7577].…”
Section: Discussionmentioning
confidence: 99%
“…Then Prime Minister, Tony Blair, championed the project, with the aim of creating a digitised, interoperable, health infrastructure that would transform healthcare delivery, achieve major improvements in health outcomes and, at the same time, substantially reduce government expenditure on healthcare. The study by Franklin et al 2 represents the long-awaited independent academic evaluation of the Electronic Prescription Service (EPS), a core component of NPfIT that aimed to reduce the need for patients to manually transfer paper prescriptions provided by their general practitioners to dispensing pharmacies and, more importantly, diminish medication errors and thereby improve patient outcomes. Franklin et al evaluated the impact of electronic transmission of prescriptions between prescribers and pharmacies, but found no benefit.…”
mentioning
confidence: 99%
“…Inexactly or incorrectly entered prescription information probably results from the physician's failure to complete the prescription correctly: for example, entering prescription information in the wrong data fields or incorrectly selecting information from the system. Previous reports have shown that one reason for lack of clarity in dosage instructions is that physicians use abbreviations that may lead to the misinterpretation of instructions in pharmacies [26,37,38]. Moreover, some errors or ambiguities required clarifications from a physician, which delayed dispensing.…”
Section: Discussionmentioning
confidence: 99%